Pemberdayaan Jamaah Yasinta pada Kawasan Penyangga Industri PT PIER Melalui Tanaman Apotik Hidup - Qusairi, Ahmad; Rahmatullah, Asep; Afrija, Dino; Rahmadi, Eman (Al Mu'azarah: Jurnal Pengabdian Kepada Masyarakat, 2026)
This study empowers the Yasinta (Yasin Tahlil) Congregation in Raci Village, Pasuruan, East Java, a buffer zone of the PT PIER industrial area, to utilize communal assets for improved health and well-being. Using the Participatory Action Research (PAR) method, the program actively involves members in planning, implementation, and evaluation. The initiative promotes living pharmacy (TOGA) cultivation such as ginger, turmeric, lemongrass, and betel in household yards to enhance physical health and environmental quality while generating economic potential through herbal product processing. The results show increased awareness of preventive health, productive land use, and a shift toward healthy, eco-friendly behavior. High participation and emerging entrepreneurial initiatives highlight the community’s growing independence. This study demonstrates that religious groups like the Yasinta Congregation can effectively serve as agents of social and environmental transformation toward a healthier and more empowered society.